Cytokinin Determines Thiol-Mediated Arsenic Tolerance and Accumulation. Issue 2 (18th April 2016) - Mohan, Thotegowdanapalya C.; Castrillo, Gabriel; Navarro, Cristina; Zarco-Fernández, Sonia; Ramireddy, Eswarayya; Mateo, Cristian; Zamarreño, Angel M.; Paz-Ares, Javier; Muñoz, Riansares; García-Mina, Jose M.; Hernández, Luis E.; Schmülling, Thomas; et al.
Abstract : The phytohormone cytokinin is an essential negative regulator of the arsenic detoxification machinery and is thus a key factor in plant tolerance and adaptation to arsenic. Abstract: The presence of arsenic in soil and water is a constant threat to plant growth in many regions of the world. Phytohormones act in the integration of growth control and stress response, but their role in plant responses to arsenic remains to be elucidated. Here, we show that arsenate [As(V) ], the most prevalent arsenic chemical species in nature, causes severe depletion of endogenous cytokinins (CKs ) in the model plant Arabidopsis ( Arabidopsis thaliana ). We found that CK signaling mutants and transgenic plants with reduced endogenous CK levels showed an As(V) -tolerant phenotype. Our data indicate that in CK -depleted plants exposed to As(V), transcript levels of As(V) /phosphate-transporters were similar or even higher than in wild-type plants. In contrast, CK depletion provoked the coordinated activation of As(V) tolerance mechanisms, leading to the accumulation of thiol compounds such as phytochelatins and glutathione, which are essential for arsenic sequestration. Transgenic CK -deficient Arabidopsis and tobacco lines show a marked increase in arsenic accumulation. Our findings indicate that CK is an important regulatory factor in plant adaptation to arsenic stress.